How Oil Contracts Affect Human Rights - Mimoso, Maria João; Clara da Conceição de Sousa Alves; Diogo Filipe Dias Gonçalves; Pedro Miguel Ferreirinha Pinto Alves (European Journal of Multidisciplinary Studies, 2018)
Since the beginning of the 19th century, we have assisted major proliferation of the oil and gas industry. This phenomenon of exponential growth is due to the fact that oil companies hold the world’s oil monopoly on the extraction, processing and commercialization. Therefore, as being one of the most influential sectors in the world, is crucial to strictly regulate how oil and gas contracts concerns the potential environmental and social impacts arising from the conduct of petroleum operations and how such behavior affects the human rights. As a matter of fact, the social issues field is an emerging area, and despite such importance, oil contracts do not often deal with them in great detail, corresponding to an actual emptiness of the human rights provisions. In terms of responsibly, oil companies, have an inalienable obligation to ensure that their actions do not violate human rights or contribute for their violation. This study aims to trace a detailed analysis of the impact of the oil and gas agreements in human rights. In order to fully comprehend the deep effects of this industry, we will examine, in detail, numerous of published oil and gas agreements, as well as, decode which are the real standards and practices accepted by this industry. We will use a deductive and speculative reasoning. We will try to demonstrate how incipient and short protection is given to human rights and what responsible conducts must urgently be developed.